Drying of soybean seeds and effect on protein quality and oil extraction efficiency by extruding-expelling process - Maciel, Gisele; Wagner, Jorge Ricardo; Bartosik, Ricardo Enrique (Escola Superior de Agricultura Luiz de Queiroz (Brasil), 2023)
Soybean seeds (Glycine max) were dried under real scale conditions to different final moisture content (m.c.) (9.1, 9.7, 10.9 %, and control with 16.2 %) and processed through extruding-expelling. Results indicated that soybean seed m.c. affected the composition of the soybean expeller and, thus, the oil extraction efficiency (OEE), which increased as the seed m.c. decreased. A polynomic model was proposed for predicting OEE as a function of soybean m.c., indicating that drying soybean to 10 % resulted in an OEE of approximately 65 %. A thin layer drying experiment of soybean seeds indicated that the protein dispersibility index (PDI) was not affected as regards drying air temperatures up to approximately 69 °C, and a bi-linear model with a non-pre-established break point was fitted. The real scale drying treatment in a rack type dryer (mixed flow) did not show any effect (p > 0.05) on the PDI at 80 °C, while at 115 °C a reduction (p < 0.05) was observed (PDI reduction was 0.8 and 2.1 percentage points, respectively).